Online Platform Application Design for Local Product - A Febriansyah; H P Ningsih; D Sartika; M Taufiq (Universitas Komputer Indonesia, 2021)
Web technology development is growing rapidly because all technology's core is to make it easier for other people to create a web or find any information via the web. This study aims to design an online application/website specifically for local products that focus on fashion, especially those that have not been touched by online media at all, such as in Pasar Baru and Pasar Andir, located in the city of Bandung. This research used descriptive with a qualitative approach. This study indicates that a website can be used as a promotional medium for local clothing stores to expand marketing reach. Besides that, it can also improve the image of the local clothing company. More than that, of course, visitors can find out the latest types of branded clothing products and make sales transactions with consumers without visiting the store in person. With this website, of course, it will make it easier for customers to make purchase transactions at local brand clothing stores that are not widely known.